Hemolytic disease of the fetus and newborn due to antibodies to minor red blood cell groups: two case reports - Menuam, Tossapon; Juengpichanvanich, Nopporn; Charoenkwan, Pimlak; Sakulwattana, Monthicha; Cheepsattayakorn, Ruangrong; Fongsatitkul, Ladda; Srisupundit, Kasemsri; Tantiprabha, Watcharee; Chotinaruemol, Somporn (Biomedical Sciences and Clinical Medicine, 2024)
This study reports two cases of hemolytic disease of the fetus and newborn (HDFN) associated with antibodies to minor red blood cell (RBC) groups. Case 1 was a 35 week-gestational age (GA) female newborn, diagnosed with fetal anemia and hydrops by prenatal ultrasound. The primigravida mother had been diagnosed with beta-thalassemia/hemoglobin E disease and after being transfused, red cell alloimmunization and autoimmunization were detected during pregnancy. Antibody identification in the mother revealed anti-c, anti-E, anti-Mia and autoantibody. At birth, the patient was severely anemic and required ventilator support due to respiratory failure. Hematocrit was 15.1%. Direct and indirect antiglobulin tests (DAT and IAT) were strongly positive. Case 2 was a 36 week-GA male newborn with early onset of indirect hyperbilirubinemia and anemia. The mother had been diagnosed with systemic lupus erythematosus and transfused several times. At delivery, antibody identification revealed anti-c and anti-Mia in the mother, while DAT and IAT were positive in the newborn. Antibody identification revealed anti-c. The patient was given phototherapy. Maximum bilirubin was 16.9 mg/dL, and the lowest hematocrit was 31% on day 11.